Daya tilik diri (Self Insight), Harga diri (self esteem) dan Stigma diri (Self Stigma) serta Kualitas hidup pasien Skizofrenia di klinik Jiwa RS Jiwa Daerah Jambi - Daryanto Daryanto; Wittin Khairani (Universitas Batanghari Jambi, 2020)
Schizophrenia experienced patients tend to be chronic so that it can affect the quality of life. Research of the quality of life of schizophrenia patients in some countries is depicted the quality of life is low, but the description and relationship of self-esteem, self-esteem and self-stigma with the quality of life schizophrenia patients in Jambi area has not been researched. Unknown to self-esteem, self-esteem and self-stigma with the quality of life of schizophrenia in the clinic of the soul RSJ in Jambi region. Design research uses descriptive correlation with cross sectional approaches. The population of the study was the entire family of schizophrenia patients who visited the mental clinic of Jiwa district of Jambi in 2016 for 3795 people, samples were selected as many as 115 respondents using simple randomized techniques. Research is conducted from August to November 2017. Data was analyzed using a simple linear regression test. The results of the study are known to the average life quality of patients is 79.08. The power of self-view correlates negatively with the quality of life of schizophrenia patients (P value 0.009 < α 0.05). There is a correlation between the self-esteem and the quality of life of schizophrenia patients (P Value 0.037 < α 0.05). Negative correlation between self-Stigma and quality of life of schizophrenia patients (P Value 0.038). Self-care power, self-esteem and self-stigma are correlated with the quality of life of schizophrenia patients. RSJ nurses are expected to give the program problem solving skills and social skills training to the patient and nursing home skills in the family. Research needs to be done for the development of schizophrenia patients in the psychiatric clinic in Jambi area.